2004
DOI: 10.1111/j.1532-5415.2004.52202.x
|View full text |Cite|
|
Sign up to set email alerts
|

Transitional Care of Older Adults Hospitalized with Heart Failure: A Randomized, Controlled Trial

Abstract: A comprehensive transitional care intervention for elders hospitalized with heart failure increased the length of time between hospital discharge and readmission or death, reduced total number of rehospitalizations, and decreased healthcare costs, thus demonstrating great promise for improving clinical and economic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
1,226
2
38

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,160 publications
(1,283 citation statements)
references
References 35 publications
17
1,226
2
38
Order By: Relevance
“…2 They are more likely to be non-English speakers, 3 have lower health literacy, which can impair selfmanagement; [4][5][6] higher rates of mental health and substance abuse disorders; 7 greater exposure to social stressors; 6 and are more likely to experience hospital readmission. [8][9][10] Several care transitions programs [11][12][13][14][15][16] have demonstrated success in decreasing hospital readmissions. These programs have primarily targeted elderly Medicare populations or patients with high risk diagnoses, such as heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…2 They are more likely to be non-English speakers, 3 have lower health literacy, which can impair selfmanagement; [4][5][6] higher rates of mental health and substance abuse disorders; 7 greater exposure to social stressors; 6 and are more likely to experience hospital readmission. [8][9][10] Several care transitions programs [11][12][13][14][15][16] have demonstrated success in decreasing hospital readmissions. These programs have primarily targeted elderly Medicare populations or patients with high risk diagnoses, such as heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, to date, no single intervention has reliably reduced 30-day readmission rates. 4 Interventions are often disease-specific, [5][6][7][8] require substantial financial investments in training allied healthcare professionals, 6,9,10 or focus primarily on hospital-based discharge planning with mixed results. 4,[11][12][13] Additionally, interventions are often multifaceted, and it is difficult to identify which elements drive improvements in patient outcomes.…”
Section: The Challenge Of Ensuring Optimal Care During Transitionsmentioning
confidence: 99%
“…69 Care transitions are an active area of research, and multiple studies have shown lower rates of rehospitalization with comprehensive transitional care programs involving ''transition coaches'' or advance practice nurses providing home visits and follow-up telephone calls. 70,71 More research is needed in this area to develop simple, cost-effective care transitions programs. In the meantime, hospitalists can actively involve a multidisciplinary team (pharmacists and social workers, for example) early in the hospitalization, provide more ''patient-friendly'' discharge materials such as those available as part of the Society of Hospital Medicine's BOOST, and place targeted follow-up phone calls after discharge.…”
Section: Discharge Planning For An Elderly Patient Should Start Earlymentioning
confidence: 99%